Ikan Bandeng Tanpa Duri (Chanos chanos) sebagai Peluang Bisnis Masyarakat Desa Mootinelo, Kabupaten Gorontalo Utara, Provinsi Gorontalo - Elya Nusantari; Aryati Abdul; Rita Marsuci Harmain (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
One of the problems of the fishing community of milkfish (Chanos chanos) Mootinelo Village, North Gorontalo District was the selling price of fish is cheap. That was because the milkfish has many thorns so that less favored communities. However, milkfish has a high excess nutrients especially unsaturated fatty acids omega-3 (ω3) reached 14.2 and a protein content of 20. In relation with it, this activity aims to increase the sale value of milkfish through training activities thorn fish and diversified products. The method used was the training activities thorn fish, dan accompaniment of activities to pull out the fish milk spines to produce diversification products, followed by mentoring partner groups, especially women and households, as well as the surrounding communities who have the desire to entrepreneurship. The activities were practiced partner groups thorn fish suit the morphology and position structure thorns fish. The result was a fish without spines can be sold to consumers or processed into products, such as nuggets, meatballs, krispy milkfish, and a traditional menu of Gorontalo fish area such as rica-rica and woku fish. The conclusion is milkfish without spines have a profitable business opportunity with the increase in the selling price of milkfish without spines. It can increase the income of fishing communities in the fish ponds in the Mootinelo Village, North Gorontalo District.